An interdisciplinary adventure into the worlds of teaching and practical theology - Botha, Carolina S. (Verbum et ecclesia, 2014)
A constant challenge to researchers and academic scholars in practical theology is to stay relevant and up to date with the constantly evolving academic concepts in which they discourse. These interactions between individuals and intellectual fields often allow for what Julian Müller terms a ‘moment of praxis’ within their epistemology that functions as a meeting place between different ideas, paradigms and often even different academic disciplines.Intradisciplinary and/or interdisciplinary implications: This article investigated the possibility of creating an interdisciplinary epistemology between practical theology and teaching. By exploring the role that post foundationalist discourse and interdisciplinary conversations can play in identifying and addressing challenges which face teaching, new light can be shed on the relationship between teaching and practical theology which thus highlights correlations between these two relevant fields.